Batch sorption studies of toxic methylene blue dye onto chitosan Capsella bursa-pastoris composite microbeads - Temiz, Ruhsen; Isik, Birol; Ugraskan, Volkan; Cankurtaran, Ozlem (SPRINGER HEIDELBERG, 2023)
Bio-based materials are promising adsorbents due to their sustainability, environmentally friendly nature, low cost, and high removal efficiency. In this study, it was aimed to investigate the Capsella bursa-pastoris-filled chitosan biocomposite microbeads for the adsorptive removal of methylene blue dye from an aqueous solution. Firstly, the biocomposite beads were prepared by the addition of different weight ratios of Capsella bursa-pastoris in chitosan gel, followed by a cross-linking process. Then, optimum adsorption conditions were determined by performing studies under different conditions, namely, temperature (25-45 degrees C), pH (2-12), contact time (0-210 min.), adsorbent amount (0.010-0.300 g), and dye concentration (10-50 ppm). The experimental data were applied to non-linear and linear Langmuir and Freundlich isotherm models, and the most suitable isotherm model for the adsorption process was determined as well as to pseudo-first-order and pseudo-second-order kinetic models, and the mechanism of the adsorption process was determined. As a result of the studies, it was obtained that the adsorption capacity of the composites increased with the increasing amount of Capsella bursa-pastoris, and the maximum adsorption capacity was found as 222.22 mg/g at 25 degrees C. From the reusability studies, it was obtained that the composite beads remain efficient after the 5(th) cycle. This study suggests that Capsella bursa-pastoris-filled chitosan biocomposite microbeads are efficient and reusable adsorbents for the removal of methylene blue dye. Graphical Abstract
Keywords: Capsella bursa-pastoris; Chitosan; Methylene blue; Microbeads; EFFICIENT REMOVAL; AQUEOUS-SOLUTION; LEAD II; ADSORPTION; EQUILIBRIUM; HYDROGEL; ADSORBENT; KINETICS; FABRICATION; BEADS; Energy & Fuels; Engineering